Developing a conceptual framework for (educational service) marketing competencies of faculty members - Shirpour, Mohsen; Sattari, Sadraddin; Vazifeh, Rasool (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The present study was to establish a conceptual framework for faculty members' personal marketing (training services) competencies. Assuming that universities are the highest institutes of learning with the aim of promoting knowledge transfer, providing human resource training in various fields of science and technology, providing higher education and research services; They need competent faculty members to achieve these goals. In this qualitative study, documentary analysis was used to evaluate all books, print and electronic resources and resources in the fields of marketing and branding, using note-taking forms as data collection tools. Qualitative analysis and further coding were used to analyze the data. The results of expert opinions also showed that one of the most important personal marketing competencies of faculty members is a significant relationship between knowledge competencies and behavioral competencies.